Best collaborative practices for advocacy and promotion of Open Educational Resources - Koutsileou, Stamatina; Anastasopoulou, Christina; Christaki, Stavroula; Mitrou, Nikolaos (Journal of Integrated Information Management, 2019)
Purpose – The present study, after reviewing the relevant literature and the recent trends that became evident from the Open Education Global Conference 2018 (and other similar fora), documents the best practices to be adopted by the Greek academic libraries, in order to support the OER actions in Higher Education by making the Academic Community aware of the culture of OER adoption/use. Design/methodology/approach – It emerged from the analysis of the empirical results of a relevant research conducted among faculty of Greek Universities. The research inquired into the support/guidance that academic libraries offer to the faculty of their institutions for: a. adopting/using Open Educational Resources (OER), b. creating OER and c. OER intellectual property (copyright). Findings – The results of the research showed that most of the faculty does not consider academic libraries much supportive of them in any of the three areas investigated -as opposed to what occurs in Europe and internationally. Originality/value – The practices documented could: a. gain advantage from the existing library infrastructure and enhance the know-how and digital competence of librarians in the following areas: OER location, intellectual property (copyright), metadata and quality assurance, institutional repositories (storage and preservation), b. support faculty and students in cultivating their digital skills and thus achieving “OER Literacy”.